2009
DOI: 10.1007/s11250-009-9403-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of major genes for crested-head, frizzle-feather and naked-neck on body weights and growth patterns of indigenous chickens reared intensively in Kenya

Abstract: The influence of major genes for crested-head (Cr), frizzle-feather (Fr) and naked-neck (Na) on body weights and growth patterns of indigenous chickens reared intensively was investigated and compared with normal-feather (na) gene. Birds were individually weighed at hatch and every two weeks up to 30 weeks of age. Growth patterns were modelled using the Gompertz-Laird function. The genes influenced body weights and growth patterns at various ages. The Cr gene had significant (P < 0.05) negative effects on body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…The high performances for IC in medium-to high-potential agricultural zones than those in the ASALs could be due to better management in terms of feeding and housing which allows chickens to express their genetic potentials. This concurs with previous studies which have reported an improved performance of IC in semi-intensive and intensive production systems (Magothe et al 2010;Ochieng et al 2011). This implies that the performance of IC can be improved by good management.…”
Section: Indigenous Chicken Management Practicessupporting
confidence: 93%
“…The high performances for IC in medium-to high-potential agricultural zones than those in the ASALs could be due to better management in terms of feeding and housing which allows chickens to express their genetic potentials. This concurs with previous studies which have reported an improved performance of IC in semi-intensive and intensive production systems (Magothe et al 2010;Ochieng et al 2011). This implies that the performance of IC can be improved by good management.…”
Section: Indigenous Chicken Management Practicessupporting
confidence: 93%
“…Patra et al (2002) identified higher body weight from 4th week onwards in NaNa genotype. Reddy et al (2008) observed lower (877.60±0.10 g) 6th week body weights in naked neck gene line compared to the present findings and might be due to favourable effects of selection and feeding regimens followed and other managemental variations like environmental temperature and season (2010) and Magothe et al (2010) reported lower body weights for naked neck genotypes than their normal counter parts from Kenya under free range conditions and temperate conditions, respectively. The higher body weight obtained in the present study indicates a more pronounced effect of Na gene in response to tropical climatic conditions.…”
Section: Resultscontrasting
confidence: 51%
“…In some literature, Eq. (2) is named as the Gompertz-Laird model (Nahashon et al, 2010;Roush and Branton, 2005;Miguel et al, 2007;Magothe et al, 2010). This model is more commonly used than its original form, therefore, the Gompertz-Laird model is used for describing the evolution of biogas consumption in rural China.…”
Section: Gompertz-laird Modelmentioning
confidence: 99%